Inhibition of germinal vesicle breakdown in Xenopus oocytes in vitro by a series of substituted glycol ethers. Issue 5 (4th December 2017) - Fort, Douglas J.; Mathis, Michael B.; Guiney, Patrick D.; Weeks, John A.
Abstract: A 24 hour in vitro Xenopus oocyte maturation (germinal vesicle breakdown [GVBD]) assay developed by Pickford and Morris ( Environmental Health Perspectives, 1999, 107, 285–292) was used to screen a series of substituted glycol ethers (GEs). Substituted GEs included: ethylene glycol monomethyl ether (EGME); EG monoethyl ether (EGEE); EG monopropyl ether (EGPE); EG monobutyl ether (EGBE); EG monohexyl ether (EGHE); diethylene glycol monomethyl ether (DGME); triethylene glycol monomethyl ether (TGME); ethylene glycol monophenyl ether (EGPhE); EG monobenzyl ether (EGBeE); EG diphenyl ether (EGDPhE); and propylene glycol monophenyl ether (PGPhE). The GEs inhibited progesterone‐ or androstenedione‐induced GVBD with the following relative potency: EGPhE > PGPhE > EGME >> EGEE ≥ EGBeE > EGPE >> EGBE >EGHE > EGDPhE >> DGME ≥ TGME, or EGPhE >> PGPhE >> EGBeE > EGDPhE > EGEE > EGME > EGPE > EGBE, EGHE, DGME and TGME, respectively. Further, [ 3 H]progesterone or [ 3 H]androstenedione binding affinities to the oocyte plasma membrane progesterone receptor (OMPR) or classical androgen receptor (AR) were: EGME > EGPhE ≥ PGPhE ≥ EGEE > EGBeE >> EGPE >> EGBE ≥ EGHE > EGDPhE, TGME, and DGME, or EGPhE > PGPhE >> EGBeE > EGDPhE >> EGEE ≥ EGME >> EGPE, EGBE, and EGHE > DGME and TGME, respectively. Binary joint mixture studies with the GVBD model using flutamide (AR antagonist) and EGPhE indicated that flutamide/EGPhE mixture acted in a concentration additive manner. The effects of substituted GE series, however, may be mediated through the OMPR; the potency of EGPhE may be the result of bimodal inhibition of both the OMPR and AR pathways. Abstract : A 24 hour in vitro Xenopus oocyte maturation assay was used to screen chemicals for endocrine disruption activity. Results suggested, however, that effects substituted GE series might be mediated through the oocyte plasma membrane receptor; the potency of ethylene glycol monophenyl ether may be the result of bimodal inhibition of both the oocyte plasma membrane receptor and androgens via a classical androgen receptor pathways.